Nutrition and Immunity 2019
DOI: 10.1007/978-3-030-16073-9_22
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Flavonoids: Possible Induction of T CD4+ Regulatory Cells Through Suppression of mTOR Pathway Signaling Activity

Abstract: The increasing rate of autoimmune disorders and cancer in recent years has been a controversial issue in all aspects of prevention, diagnosis, prognosis and treatment. Among dietary factors, flavonoids have specific immunomodulatory effects that might be of importance to several cancers. Over different types of immune cells, T lymphocytes play a critical role in protecting the immune system as well as in the pathogenesis of specific autoimmune diseases. One of the important mediators of metabolism and immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 112 publications
0
18
0
Order By: Relevance
“…Luteolin had potent activity against wild-type and clinical isolates of HSV-2 (EC 50 22.4 and 27.5 µg/ml and EC 99 at 40.2 and 49.6 µg/ml ( Ojha et al ., 2015 ), and replication of dengue virus via Furin proprotein convertase inhibition ( Peng et al ., 2017 ). Additionally, luteolin possess anti-seditious ( Aziz et al ., 2018 ) and immunomodulatory activity ( Hosseinzade et al ., 2019 ). However, the designed and predicted Phyto-compounds needs to have interacted with the host cell surface receptor with optimal inhibition, as well as constant and stable binding at pharmacological relevant concentration.…”
Section: Host Cell Receptors and Their Role On Covid-19 Virus Entry Pmentioning
confidence: 99%
“…Luteolin had potent activity against wild-type and clinical isolates of HSV-2 (EC 50 22.4 and 27.5 µg/ml and EC 99 at 40.2 and 49.6 µg/ml ( Ojha et al ., 2015 ), and replication of dengue virus via Furin proprotein convertase inhibition ( Peng et al ., 2017 ). Additionally, luteolin possess anti-seditious ( Aziz et al ., 2018 ) and immunomodulatory activity ( Hosseinzade et al ., 2019 ). However, the designed and predicted Phyto-compounds needs to have interacted with the host cell surface receptor with optimal inhibition, as well as constant and stable binding at pharmacological relevant concentration.…”
Section: Host Cell Receptors and Their Role On Covid-19 Virus Entry Pmentioning
confidence: 99%
“…increases phagocytic activity possibly affected by flavonoids contain in it characterized by increased levels of CD 4+ and CD 14 cells, although the exact mechanisms are not well understood. 16…”
Section: Resultsmentioning
confidence: 99%
“…Among other roles, PIs act as substrates of phosphatidylinositol 3-kinases (PI3K), which catalyze their phosphorylation to phosphatidylinositol phosphates (PIP), known to act as second messengers in multiple cellular processes [ 36 ]. The ability of flavonoids like quercetin and fisetin to inhibit the PI3K signaling pathway has been linked mostly to their anticancer activity, while its relation to immune responses is still unclear [ 12 ]. Our results further showed that several PS species decreased upon quercetin treatment, while displaying increased levels in naringin-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the modulation of immune cells’ intracellular metabolism has also been associated with the anti-inflammatory activity of flavonoids. These compounds were proposed to suppress the glycolysis-promoting PI3K/Akt/mTOR pathway in T helper (Th) inflammatory cells, leading to induction of T regulatory cells [ 12 ]. Moreover, flavonoid-mediated metabolic reprogramming of macrophages has been previously reported by us [ 13 ].…”
Section: Introductionmentioning
confidence: 99%